Voltammetric Determination of the Herbicide Linuron Using a Tricresyl Phosphate-Based Carbon Paste Electrode - Dordević Jelena; Papp Zsigmond; Guzsvány Valéria; Švancara Ivan; Trtić-Petrović Tatjana; Purenović Milovan; Vytřas Karel (Molecular Diversity Preservation International, 2012)
This paper summarises the results of voltammetric studies on the herbicide 3-(3,4-dichlorophenyl)-1-methoxy-1-methylurea (Linuron), using a carbon paste electrode containing tricresyl phosphate (TCP-CPE) as liquid binder. The principal experimental conditions, such as the pH effect, investigated in Britton-Robinson buffer solutions (pH 2.0-7.0), the peak characteristics for the analyte of interest, or instrumental parameters for the differential pulse voltammetric mode were optimized for the method. As found out, the best electroanalytical performance of the TCP-CPE was achieved at pH 2.0, whereby the oxidation peak of Linuron appeared at ca. + 1.3 V vs. SCE. The analytical procedure developed offers good linearity in the concentration range of 1.25-44.20 mu g mL(-1) (1.77 x 10(-4)-5.05 x 10(-6) mol L-1), showing-for the first time-the applicability of the TCP-CPE for anodic oxidations in direct voltammetry (without accumulation). The method was then verified by determining Linuron in a spiked river water sample and a commercial formulation and the results obtained agreed well with those obtained by the reference HPLC/UV determination.
Voltametrické stanovení herbicidu Linuronu pomocí uhlíkové pastové elektrody s trikresyl-fosfátem
Keywords: linuron; herbicide; carbon paste electrode; tricresyl phosphate; differential pulse voltammetry; uhlíková pastová elektroda; Linuron; herbicidy; trikresyl-fosfát, diferenční pulsní voltametrie